Analisis Beban Kerja Karyawan Perakitan Kemasan Bedak untuk Memenuhi Permintaan - Rifaldi, Moch Fiqi; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. XYZ is a Foreign Investment (PMA) company that specializes in the plastic cosmetic packaging printing industry and produces more than a thousand packaging variants. This research focuses on the assembly part of the DK-274 baby powder packaging. The problem found in this research is the delay in achieving the demand target which originates from worker fatigue due to work pressure and other factors during the production process. In this research, workload measurements will be carried out and determine the optimal or ideal number of workers to meet demand. By using several research methods, including work sampling and work load analysis (WLA), which functions to determine the workload and the optimal number of workers. After the method was applied, the results showed that assembly of the DK-274 baby powder packaging product required a manufacturing time of 1.40 minutes per product unit with an average workload of 109.04% (overload). From the results of this research, the labor solution used in assembly DK-274 baby powder packaging uses 7 workers and 1 automatic press machine. By calculating using work load analysis, it was found that there was no additional workforce. The production alternative requires the company to provide overtime for 7 workers. With this implementation, the company only incurs less costs compared to increasing the number of workers